A Review of Probe-Based Confocal Laser Endomicroscopy for Pancreaticobiliary Disease - Kunal Karia; Michel Kahaleh (Korean Society of Gastrointestinal Endoscopy, 2016)
Confocal laser endomicroscopy (CLE) is a novel in vivo imaging technique that can provide real-time optical biopsies in the evaluation of pancreaticobiliary strictures and pancreatic cystic lesions (PCLs), both of which are plagued by low sensitivities of routine evaluation techniques. Compared to pathology alone, CLE is associated with a higher sensitivity and accuracy for the evaluation of indeterminate pancreaticobiliary strictures. CLE has the ability to determine the malignant potential of PCLs. As such, CLE can increase the diagnostic yield of endoscopic retrograde cholangiopancreatography and endoscopic ultrasound, reducing the need for repeat procedures. It has been shown to be safe, with an adverse event rate of ≤1%. Published literature regarding its cost-effectiveness is needed.